An integrated geospatial modelling framework of hybrid microgrid sizing for rural electrification planning - Berino Francisco Silinto; Darlain Edeme; Silvia Corigliano; Aleksandar Dimovski; Marco Merlo; Christian Zuidema; André Faaij (MethodsX, 2025)
Pursuing rural electrification in developing countries through hybrid generation systems is constrained by a lack of suitable energy modelling tools. Few tools include geographical parameters relevant to capturing specific spatial and socio-economic circumstances. Even less are openly available and find applications for rural areas of developing countries. This work presents an integrated geospatial energy modelling framework based on an extended tool, the GISEle (GIS for rural electrification) model, which aims for a least-cost energy solution. GISEle is an open-source tool supporting rural electrification planning strategies and challenges through optimal hybrid microgrid integration. The developed framework is universally applicable and explains how the extended GISEle tool can be used to become suitable for analysing decentralised hybrid generation systems within the context of rural areas of developing countries. This presented framework includes: • Advancing the approach to proper data collection to better capture local specificities and (future) demand and reporting results in rural areas of developing countries; • Adding the Remote-Areas Multi-energy systems load Profiles (RAMP) to improve load demand assessments, while considering the impact of electrification on growing demand scenarios; • Linking the Soil and Water Assessment Tool (SWAT) model to allow for hydropower sizing in GISEle.